Successful ventilation through a Rüsch intubation guide catheter in severe laryngotracheal stenosis - Victoria Van Regemorter; Arnaud Potié; Sandra Schmitz; Jean-Louis Scholtes; Laurent Veevaete; Michel Van Boven (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Providing adequate ventilation may remain complex in patients with severe proximal laryngotracheal stenosis, especially when the airway is shared with the surgeon during tracheal resection surgery. We describe an effective alternative to standard endotracheal intubation using a Rüsch flexible intubation guide catheter. Methods In two patients undergoing tracheal repair surgery, we failed to insert a 5.0 inner diameter endotracheal tube (6.9 mm outer diameter) or a 6.0 mm outer diameter endoscope through the laryngotracheal stenosis. However, using indirect laryngoscopy, a 6.0 outer diameter Rüsch flexible intubation guide catheter was passed successfully through the vocal cords and then through the stenosis. Controlled ventilation was achieved by means of the Rüsch guide, provided with its two large Murphy’s eyes. When the trachea was opened, the Rüsch guide was removed just enough for the surgeons to place a Montandon tracheal tube, at that point taking over ventilation. A 7.0 inner diameter endotracheal cuffed tube had been inserted onto the Rüsch guide and left pending upstream from the vocal cords. Once the posterior tracheal wall was sutured, this endotracheal cuffed tube was slid along the Rüsch guide through the vocal cords with the cuff placed beyond the tracheal sutures. Results Controlled ventilation through the Rüsch flexible intubation guide catheter showed satisfying and stable ventilatory parameters in both patients. Inspiratory pressures of 25–30 mmHg were enough to reach adequate tidal volumes around 450 ml. End tidal CO2 was kept between 35 and 40 mmHg (PaCO2 showed similar values). Standard endotracheal intubation at the end of the tracheal resection was easy and safe thanks to the Rüsch guide still in place between the vocal cords. Conclusions We suggest an effective and reliable method using a Rüsch flexible intubation guide catheter for airway management in patients suffering from laryngotracheal stenosis in the setting of tracheal repair surgery.